Construction and enhancement of a prototype for a medical-hospital equipment for hypodermoclysis: a qualitative study - Thayna Silva de Assis Barros; Eduardo José Ferreira Santos; Pedro Miguel dos Santos Dinis Parreira; Juliana Faria Campos; Inês Franco de Almeida; Rafael Alves Bernardes; Marcelle Miranda da Silva (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to construct a Subcutaneous Hydration Device semi-functional prototype and gather initial information to improve this prototype design and realize its acceptance potential. Methods: a qualitative, descriptive and exploratory study, which used focus group, following the Technology Acceptance Model. The group was held at the Escola Superior de Enfermagem de Coimbra, Portugal, in December 2022, composed of nine participants from six different disciplinary areas, and followed thematic analysis. Results: four topics emerged associated with the device components: elastomeric infusion pump; needle/access device; clamp; administration set. From these topics, topics were triggered that highlighted: characteristics about the target population; ease of use and accessories; patient comfort and safety; and device application context. Final Considerations: the Subcutaneous Hydration Device semi-functional prototype is viable and interesting for the clinic. The results support its improvement and direct future investments for experimental studies.